Examining Tribal Environmental Law - Warner, Elizabeth Ann Kronk (Columbia Journal of Environmental Law, 2019)
Since the revolution of environmental law began roughly forty years ago, scholars have wrestled with the complex interactions of the states and federal government, but they have largely ignored tribal governments. Although some scholarship exists regarding the suggested development of tribal environmental law, little is known about the extent to which tribes nationwide have enacted such laws. This Article fills that vacuum by taking a first look at existing tribal environmental law and exploring the laws of one tribal nation that has enacted several environmental laws. The Article also proposes some initial norms to guide the development of tribal environmental law.